2021
DOI: 10.3389/fmicb.2021.686049
|View full text |Cite
|
Sign up to set email alerts
|

Translational GTPase BipA Is Involved in the Maturation of a Large Subunit of Bacterial Ribosome at Suboptimal Temperature

Abstract: BPI-inducible protein A (BipA), a highly conserved paralog of the well-known translational GTPases LepA and EF-G, has been implicated in bacterial motility, cold shock, stress response, biofilm formation, and virulence. BipA binds to the aminoacyl-(A) site of the bacterial ribosome and establishes contacts with the functionally important regions of both subunits, implying a specific role relevant to the ribosome, such as functioning in ribosome biogenesis and/or conditional protein translation. When cultured a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 65 publications
2
2
0
Order By: Relevance
“…To the contrary, at 20°C, ESC19 cells harboring pACYC184 showed a significant reduction in 70S ribosomes and accumulation of free ribosomal subunits (right panel in Figure 5A ). In addition, an abnormal peak was observed between the two ribosomal subunits (red arrowheads in Figure 5A ), which is consistent with previous studies ( Choi and Hwang, 2018 ; Gibbs and Fredrick, 2018 ; Goh et al, 2021 ). This profile was also observed in the cells transformed with pBIS05-2.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…To the contrary, at 20°C, ESC19 cells harboring pACYC184 showed a significant reduction in 70S ribosomes and accumulation of free ribosomal subunits (right panel in Figure 5A ). In addition, an abnormal peak was observed between the two ribosomal subunits (red arrowheads in Figure 5A ), which is consistent with previous studies ( Choi and Hwang, 2018 ; Gibbs and Fredrick, 2018 ; Goh et al, 2021 ). This profile was also observed in the cells transformed with pBIS05-2.…”
Section: Resultssupporting
confidence: 92%
“…In the subunit profiles of ESC19 cells with pBIS02-2 and pBIS07-1, only a single precursor particle appeared adjacent to the 50S ribosomal subunit peak, with increased normal 50S ribosomal subunits (red arrowhead in Figure 5B ). ( Goh et al, 2021 ) Based on these findings, we confirmed that YebC could not resolve ribosomal defects in the strain ESC19. Notably, ESC19 cells expressing either L20 or NhaR exhibited almost identical polysome and subunit profiles, implying that suppressive NhaR may be able to promote ribosome biogenesis at low temperature.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Era is an essential protein and is one of the multiple ribosome-associated GTPases (RA-GTPases). In addition to Era, RA-GTPases such as RsgA, Der, BipA, and ObgE function in various stages of the ribosome assembly process ( Britton, 2009 ; Gibbs et al, 2020 ; Goh et al, 2021 ). Era binds near the 3′ end of the 16S rRNA of the 30S subunit ( Sayed et al, 1999 ; Tu et al, 2009 , 2011 ).…”
Section: Introductionmentioning
confidence: 99%